Migrants’ Stories of Everyday Life: An Ethnographic Account - Pun, Lal Bahadur (Journal of Education and Research, 2018)
This article discusses migrants’ stories of everyday life. The migrants inscribe their different stories in the new contexts and social systems. After mirroring migrants’ first-hand stories, those stories are retold by migrants themselves and also by readers or audiences. The retelling of those stories reveals the reflections of individuals, groups, or on any social events or ceremonies. Against this background, this article aims at explicating how migrants coin their stories in the social worlds, which they practise in their everyday life. As a narrative ethnographer, I have attempted to knit the stories of two migrants from Bharse in Gulmi District, Nepal, who have been currently living in Kathmandu. Based on informal conversations and interactions with the migrants and observations of their everyday life, I have garnered their stories. The findings reveal that the changing socio-cultural contexts, over time and space, lead to the germination of new stories of the everyday life of the migrants. Moreover, the migrants engage in diverse social rules, regulations and value systems, as these attributes are required for behavioural change and social adaptation. Above all, the migrants embody multiple stories in their everyday life because of their knowledge and experiences of the places of their origin and destination.